Posterior Microphthalmia, A Challenging Diagnosis - , Kalimullah Shaikh, Nazia Qidwai (Pakistan Journal of Ophthalmology, 2015)
Microphthalmia involves eyes with total axial length of at least 2 standard deviations below age-similar controls. This case report presents an unusual form of microphthalmia, the posterior microphthalmia which has never been reported in Pakistan before. It also emphasises on the importance of use of Optical coherence tomography (OCT) for the diagnosis of posterior micropohthalmia. A 7 year old boy presented to us with bilaterally decreased vision and was found to have bilateral high hypermetropia. His fundal examination showed blurred optic disc margins and dolphin - shaped elevated pappillomacular fold extending from the fovea to the optic disc in both the eyes. OCT showed elevated neurosensory retina with normally attached retinal pigment epithelium. This confirmed the diagnosis of posterior Microphthalmia. The use of OCT thus aids in not just establishing the diagnosis of posterior microphthalmia but also prevents us from developing the wrong diagnosis of papilledema and carrying out any unnecessary investigations. Key words: Posterior microphthalmia, High hypermetropia, Optical coherence tomography, Pseudopapilledema.